Nanjing Eco Island Exhibition Center - Jay Siebenmorgan (Oz, 2017)
Full-Text Currently Unavailable - Nanjing, China, serves as one of the world’s largest inland ports and a major center of culture, education, economy, and tourism.Commissioned through a design contest hosted by the national government in 2010, the Eco Island Exhibition Center reflects a forward-thinking optimism, physically manifested and symbolized in the horizon, situating a place between the rich local history and the future of Nanjing.